Adipocyte-secreted BMP8b mediates adrenergic-induced remodeling of the neuro-vascular network in adipose tissue. Issue 1 (December 2018) - Pellegrinelli, Vanessa; Peirce, Vivian; Howard, Laura; Virtue, Samuel; Türei, Dénes; Senzacqua, Martina; Frontini, Andrea; Dalley, Jeffrey; Horton, Antony; Bidault, Guillaume; Severi, Ilenia; Whittle, Andrew; et al.
Abstract Activation of brown adipose tissue-mediated thermogenesis is a strategy for tackling obesity and promoting metabolic health. BMP8b is secreted by brown/beige adipocytes and enhances energy dissipation. Here we show that adipocyte-secreted BMP8b contributes to adrenergic-induced remodeling of the neuro-vascular network in adipose tissue (AT). Overexpression ofbmp8b in AT enhances browning of the subcutaneous depot and maximal thermogenic capacity. Moreover, BMP8b-induced browning, increased sympathetic innervation and vascularization of AT were maintained at 28 °C, a condition of low adrenergic output. This reinforces the local trophic effect of BMP8b. Innervation and vascular remodeling effects required BMP8b signaling through the adipocytes to 1) secrete neuregulin-4 (NRG4), which promotes sympathetic axon growth and branching in vitro, and 2) induce a pro-angiogenic transcriptional and secretory profile that promotes vascular sprouting. Thus, BMP8b and NRG4 can be considered as interconnected regulators of neuro-vascular remodeling in AT and are potential therapeutic targets in obesity. Enhancing thermogenesis is a promising therapeutic strategy for promoting metabolic health. Here the authors show that adipocyte-secreted BMP8b contributes to optimizing the thermogenic response by remodeling of the neuro-vascular networks in brown and white adipose tissue.